Adverse Pregnancy Outcomes Associated with Three Gram-negative Bacteria Found at Low Frequencies in Female Genital Microbiomes - George L. Mendz (Challenges in Disease and Health Research Vol. 5, 2021)
Acinetobacter, Hafnia and Campylobacter are three Gram-negative bacterial genera involved with low frequencies in genital infections that result in adverse pregnancy outcomes. This study reviews characteristics of the microbiology, epidemiology, diagnosis and treatment of each of these taxa, and describes several specific cases of maternal and infant infections that illustrate problems encountered with these pathogens and in the treatments of maternal and neonate infections. It is concluded that cultivation-independent investigations to identify and characterise the bacteria that cause intra-amniotic infections associated with histological chorioamnionitis and spontaneous preterm birth will reveal species that warrant further study. This knowledge, in conjunction with the application of improved microbial detection methods in the clinical setting will facilitate the development of new prevention, diagnosis and treatment strategies.